Spatiotemporal evolution of hedging effects in Asia-Pacific countries amid Sino-US competition: Insights from massive event data - Qiyue Hu; Lihua Yuan; Bin Liu (PLoS ONE, 2025)
Facing the pressure of Sino-US strategic competition, countries in the Asia-Pacific region often adopt hedging strategies to minimize risk and protect their interests. If implemented, these strategies could impact relationships between countries and lead to political instability. Owing to a lack of theoretical evaluation frameworks and methods, few studies have examined the implementation effects of hedging strategies adopted by Asia-Pacific countries amid Sino-US competition. This study proposes a novel four-quadrant evaluation theoretical framework, and constructs a Geopolitical Relation Index and a Comparative Relation Index based on the Global Database of Events, Language, and Tone massive event data. Since 2000, the effects of hedging strategies in 19 Asia-Pacific countries against China and the US have been dynamically quantified. The research reveals that Asia-Pacific countries’ dynamic performances over 24 years can be categorized into three groups: significantly closer to China, significantly closer to the US, and swinging. Since implementing the Belt and Road Initiative, countries close to China have deepened their ties, while those aligned with the US have strengthened their ties. Asia-Pacific countries have demonstrated similar characteristics from Obama’s presidency to Biden’s presidency. The results contribute to the dynamic assessment and ongoing monitoring of the execution effects of Asia-Pacific countries’ diplomatic strategies towards China and the US, offering valuable insights for timely refinement of their foreign policies.